SECONDARY PROPHYLAXIS OF VENOUS THROMBOEMBOLISM (VTE) WITH LOW DOSE APIXABAN OR RIVAROXABAN: RESULTS FROM A PATIENT POPULATION WITH MORE THAN 2 YEARS OF MEDIAN FOLLOW-UP - Alessandro Laganà; Giovanni Manfredi Assanto; Chiara Masucci; Mauro Passucci; Livia Donzelli; Alessandra Serrao; Erminia Baldacci; Cristina Santoro; Antonio Chistolini (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Direct oral anticoagulants (DOACs) are widely used for the treatment and secondary prophylaxis of venous thromboembolism (VTE). Nowadays, DOACs represent the gold standard for long-term anticoagulation, with low-intensity DOACs administration becoming increasingly used worldwide in such scenario. Albeit low-intensity apixaban and rivaroxaban are approved for clinical usage as secondary VTE prophylaxis, there are few literature data regarding their efficacy and safety with a long follow-up.